Social marketing in HIV/AIDS prevention: its contribution and challenges - Tham, Jen Sern (Human Resource Management Academic Research Society, 2023)
In the realm of public health promotion, where pharmacological, immunological, and medical interventions may not be readily available, an alternative approach has gained prominence—social marketing. This innovative strategy applies commercial marketing techniques to create and execute programs and campaigns that have a sustainable impact on target populations. It has been increasingly adopted by health practitioners and departments as a means to promote beneficial behavioral changes within society. However, in Malaysia, social marketing is still a relatively new concept, and its significance in addressing health issues, particularly in the context of HIV/AIDS, is not widely understood. Raising awareness about the importance and principles of social marketing is crucial in tackling public health challenges effectively. By integrating social marketing into health promotion efforts, Malaysia can harness the power of strategic communication, behavior analysis, and consumer insights to promote positive health behaviors. The potential for social marketing to influence attitudes, beliefs, and practices related to HIV/AIDS prevention and treatment is significant. Efforts are underway to familiarize Malaysians with social marketing and its applications in public health. Through education, training, and collaborative initiatives, the aim is to empower health professionals, policymakers, and the public to embrace this approach and leverage its potential in creating lasting positive change. By adopting social marketing strategies, Malaysia can enhance its response to health challenges, including the prevention and management of HIV/AIDS, ultimately leading to improved health outcomes for its population.